Faktor-Faktor yang Mempengaruhi Kepuasan Mahasiswa pada Universitas Bina Nusantara - Reina Reina (Binus Business Review, 2012)
This study aims to determine the factors that influence student satisfaction of service quality. The research methodology used correlation effects of independent variables, namely the factors of service quality; reliability, responsiveness, assurance, empathy, and tangibles against the dependent variable, the satisfaction of students. The results showed that the five dimensions of service quality is significant influence on student satisfaction. BINUS University needs to improve the quality of service to increase the level of student satisfaction.